The Impact Of Change-Oriented Leadership On Voice Behavior And Intent To Quit With Employee Personality As Moderator And Perceived Issue Threat As Mediator - Muna Ibrahim G. Alyusef; PengCheng Zhang (European Scientific Journal, ESJ, 2016)
Change-oriented leadership is a specific leadership style in encouraging employee voice behaviors. In present day, voice is regarded as an essential tool in improving the performance of any organization. Employee voice acts as a driving factor in influencing organizational change and suggesting innovative ideas. Employee personality moderates the relationship between change-oriented leadership and perceived issue threat. When employees feel they will not be treated unjustly and are free to express their ideas, they are more likely to voice their opinions without hindrance. Moreover, by anticipating positive responses from the manager, employees are more likely to have trust in management to appreciate their input; hence managerial openness is a positive indicator of voice behaviors and intent to quit. This study has four propositions. The first states that transformational leadership has a positive impact on voice behaviors and intent to quit. Secondly, managerial openness has a positive impact on voice behaviors and intent to quit. Thirdly, employee personality moderates this relationship while lastly; perceived issue threat mediates this relationship. The study concludes in the acceptance of these propositions. Researchers should explore the diversity factors associated with change-oriented leadership and voice behaviors.